AUTHENTIC LEADERSHIP AND WORKING HOURS EFFECT ON HOTEL WORKER'S PERFORMANCE MEDIATED BY WORKERS SATISFACTION - Fiona Cherenenita; Helma Malini; Ilzar Daud; Ahmad Shalahuddin; Sulistiowati Sulistiowati (SEAN Institute, 2023)
The hotel industry sector is experiencing a very rapid revitalization of business conditions due to economic conditions and tourism recovery. Improving management performance is the key to maintaining a position in competition. One of the crucial factors in improving management performance is characterized by good employee performance. Employee performance itself is influenced by several factors, namely leadership, working hours, and job satisfaction. This research aims to explore the relationship between each variable in several hotels in West Kalimantan using a quantitative approach with causal associative research methods. AMOS will then assist in research analysis. This research used a questionnaire to collect data from 215 respondents who were employees of several-star hotels in West Kalimantan.